Pengaruh Mental Health Dan Workplace Well-Being Terhadap Kinerja Aparatur Pemerintahan Desa - Rohmatul Aminah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study aims to analyze the influence of mental health and workplace well-being on the performance of village government officials. A qualitative descriptive approach was employed, using interviews and documentation as data collection techniques involving eight village officials in Mojokerto Regency. The findings indicate that mental health, workplace well-being, work–life balance, and organizational support significantly affect the performance of village officials. Support in the form of effective communication, health insurance, and a conducive work environment contributes to improving employee well-being and productivity. However, the demand for public services that operate 24 hours a day remains a major challenge in maintaining a balance between work and personal life. This study concludes that workplace well-being and mental health have a positive impact on the performance of village government officials, highlighting the need for improved policies to support employees’ physical health, mental health, and overall quality of work life.